Edutainment at the higher education as an element for the learning success - Banek Zorica, Mihaela (Array, 2014)
The notion that education and learning can be linked with lucid, playful and pleasurable experiences is not new. Gros (2003) defines edutainment as education that has been placed within the framework of entertainment. The introduction of computers and the Internet has affected traditional educational environments, enabled implementation of a large variety of edutainment types in the learning process thus radically transforming educational paradigm by strengthening the relationship between learning, new media and play. Although, elements of edutainment were already implemented in the educational process sporadically with the advancement of ICT it has become immensely popular and commercially successful with students, teachers, parents and children. In the past, however, edutainment existed but it was not highly utilized as today while today we are facing a growing number of adults that have grown up with technology, entertainment and computer games. We could say that digital natives (Prensky 2001) who recently were a discussed as students and learners are now grownups entering educational process as teachers. Paper examines how ICT through new media and game-based learning has enhanced educational process. Edutainment is an ever expanding arena for new products and new ways of incorporating technology and fun into the learning process. Author gives an overview of the edutainment field presenting its strengths and weaknesses. The theoretical background is used to classify types of edutainment and discus the new phenomenon of academia and business collaborating in developing high quality multimedia and game-based content. The main purpose of edutainment is to promote student learning through usage of entertainment which has become more accessible and easier to incorporate into the educational process. In the end results of the pilot project of implementing edutainment at the higher education are presented.